(untitled) (Journal of Engineering, 2008)
Sodium Lauryl Ether Sulfate (SLES) with five different concentrations (from 50 to 100 ppm) were used as drag reducer. This surfactant was studied using gasoil with seven different fluid flow rates (from 1.9 to 4.5 m3 /h) and a testing section length of 4 m. Percentage drag reduction (%Dr) was found to increase by increasing the surfactant concentration and Reynolds number. Maximum drag reduction (45.5%) was acheved by using 300 ppm of SLES dissolved in gas oil for flow rate equals to 4.5 m3 /h. Friction factor was calculated from the experimental data. For pure solvent; friction factor values lies near or at Blasuis asymptote. While, by producing the surfactants into the flow, the friction factor values were positioned below Blasius asymptote towards Virk maximum drag reduction asymptote. Correlation equation was suggested for surfactant solutions. This correlation shows the friction factor as a function of Reynolds number (Re) and surfactant concentration (C). The results showed good agreement between the observed friction factor values and the predicted ones from the correlation equation.